(untitled) (Journal of Atomic and Molecular Sciences, 2018)
Adipocyte fatty-acid binding protein (A-FABP) is abundantly expressed in macrophage and adipocyte, and it is a potential target for the treatment of atherosclerosis and metabolic disease. In this work, binding differences of two inhibitors ACD and TDZ to A-FABP were studied by using principal component (PC) analysis, molecular mechanics generalized Born surface area (MM-GBSA) and solvated interaction energy (SIE) methods. The results show that the binding of inhibitor TDZ to A-FABP is stronger than that of ACD to A-FABP. The calculation of residue-based free energy decomposition and dynamics analysis of hydrogen bonds suggest that hydrophobic interactions and hydrogen bonding interactions play important roles in the structural stability of A-FABP. The information obtained from this work will provide a useful clue for design of effective drugs targeting A-FABP.